Across the Green Sea : histories from the Western Indian Ocean, 1440-1640 - Subrahmanyam, Sanjay (University of Texas Press, 2024)
"This book connects histories from shifting viewpoints around the Western Indian Ocean showing the complexity of a dynamic oceanic system both before and after the arrival of Europeans"-- Provided by publisher.
Keywords: Indian Ocean Region -- History -- 15th century.; Indian Ocean Region -- History -- 16th century.; Indian Ocean Region -- History -- 17th century.; Indian Ocean -- Navigation -- History -- 15th century.; Indian Ocean -- Navigation -- History -- 16th century.; Indian Ocean -- Navigation -- History -- 17th century.; Indien, Région de l'océan -- Histoire -- 16e siècle.; Indien, Région de l'océan -- Histoire -- 17e siècle.; Indien, Océan -- Navigation -- Histoire -- 16e siècle.; Indien, Région de l'océan -- Histoire -- 15e siècle.; Indien, Océan -- Navigation -- Histoire -- 15e siècle.; Indien, Océan -- Navigation -- Histoire -- 17e siècle.; HISTORY / General; Navigation; Indian Ocean; Indian Ocean Region; 1400-1699; History